STRESS COPING STRATEGIES AMONG GHANAIAN WOMEN IN MANAGERIAL POSITIONS - Roberts, Charity (European Scientific Journal, ESJ, 2014)
The study investigated occupational stressors, their effects and the coping mechanisms that women in managerial positions adopt. Selected women in various managerial positions in Ghana were interviewed using the Occupational Stress Inventory–Revised interview guide. The results showed that stressors experienced by the women included role over-load, role insufficiency, role ambiguity, role conflict, role responsibility and physical environmental stressors. The effects of these occupational stressors included vocational, psychological, interpersonal and behavioural and physical strains. Consequently, the women employed various coping mechanisms to combat these effects and that the severity of these stressors often depended on their coping strategies. There was no evidence to suggest that these women employed popular stress reduction techniques such as autogenic or progressive muscular relaxation including yoga and formal structured physical education in coping with the stresses they experienced. The results have implications on appropriate work place environment, particularly with respect to provision of stress coping or management strategies